2005
DOI: 10.1590/s1516-635x2005000100008
|View full text |Cite
|
Sign up to set email alerts
|

Diets formulated on total or digestible amino acid basis with different energy levels and physical form on broiler performance

Abstract: We studied the effects of two different systems of expressing amino acid requirements (total - TAA or digestible - DAA), two energy levels (2,900 or 3,200 kcal of ME/kg) and two physical forms (mash or pellet) on the performance of male broilers from 21 to 42 d of age. Diets formulated on DAA basis improved feed conversion (p<0.001) and the conversion of consumed ME into body weight gain (p<0.001). Birds fed 3,200 kcal ME/kg presented better feed conversion (p<0.001), higher abdominal fat deposition (p<0.001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The physical form of pre-start diet (1-7 days) influences the performance of broilers until the end of the initial phase (8-21 days old), but the effects diminish until slaughter age with no effect on carcass characteristics (Freitas et al, 2009). Several studies are in line with the increase of broiler performance when processed diets are offered, which is mostly explained both by improvements in weight gain and feed conversion (Jones et al, 1995;Scott et al, 1997;Leeson et al, 1999;Lecznieski et al, 2001;Vargas et al, 2001;Greenwood et al, 2004;Silva et al, 2004;Maiorka et al, 2005;Lara et al, 2008); development of the digestive tract (Shamoto & Yamauchi, 2000; Feeding Behaviour of Broiler Chickens: a Review on the Biomechanical Characteristics Engberg et al, 2002;Dahlke et al, 2003;Zang et al, 2009); increasing of feed density leading both to nutrient intake and to growth rate (Engberg et al, 2002;McKinney & Teeter 2004;Lemme et al, 2006;Freitas et al, 2008;Meurer et al, 2008;Freitas et al, 2009); greater nutrient digestibility (Moreira et al, 1994;Vargas et al, 2001;Goodband et al, 2002;Freitas et al, 2008;Zang et al, 2009); reduction on particles selectivity by the birds and better palatability (Gadzirayi et al, 2006;Lara et al, 2008); minimization of energy expenditure during feeding (Nir, et al, 1994c;Leeson et al, 1999;Jensen, 2000;López et al, 2007); decreasing of wastage (Jensen, 2000;…”
Section: Feeding Behaviour Of Broiler Chickens: a Review On The Biomementioning
confidence: 85%
“…The physical form of pre-start diet (1-7 days) influences the performance of broilers until the end of the initial phase (8-21 days old), but the effects diminish until slaughter age with no effect on carcass characteristics (Freitas et al, 2009). Several studies are in line with the increase of broiler performance when processed diets are offered, which is mostly explained both by improvements in weight gain and feed conversion (Jones et al, 1995;Scott et al, 1997;Leeson et al, 1999;Lecznieski et al, 2001;Vargas et al, 2001;Greenwood et al, 2004;Silva et al, 2004;Maiorka et al, 2005;Lara et al, 2008); development of the digestive tract (Shamoto & Yamauchi, 2000; Feeding Behaviour of Broiler Chickens: a Review on the Biomechanical Characteristics Engberg et al, 2002;Dahlke et al, 2003;Zang et al, 2009); increasing of feed density leading both to nutrient intake and to growth rate (Engberg et al, 2002;McKinney & Teeter 2004;Lemme et al, 2006;Freitas et al, 2008;Meurer et al, 2008;Freitas et al, 2009); greater nutrient digestibility (Moreira et al, 1994;Vargas et al, 2001;Goodband et al, 2002;Freitas et al, 2008;Zang et al, 2009); reduction on particles selectivity by the birds and better palatability (Gadzirayi et al, 2006;Lara et al, 2008); minimization of energy expenditure during feeding (Nir, et al, 1994c;Leeson et al, 1999;Jensen, 2000;López et al, 2007); decreasing of wastage (Jensen, 2000;…”
Section: Feeding Behaviour Of Broiler Chickens: a Review On The Biomementioning
confidence: 85%
“…In addition, in many studies it was observed that pellet diets improve FCR compared to mash feed. These improvements have been associated with greater digestibility of nutrients and less feed wastage and microbial load (Kilburn & Edwards 2001, Engberg et al 2002, Maiorka et al 2005, Salari et al 2006, Amerah et al 2007, Attia et al 2012. The nutritive value of pellet diets may be improved as a result of increasing starch gelatinization in the pellet process (Heffner & Pfost 1973, Moritz et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have to be continued to decrease cost of broiler production and improve broiler performance. Pellet feed has been shown to have the greatest potential to improve feed conversion ratio (FCR) and reduce cost compared to mash feed (Maiorka et al 2005, Salari et al 2006, Amerah et al 2008. These improvements have been associated with changes in nutrients, digestibility and less feed wastage (Amerah et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent interest in poultry feed formulation has led to take into account the digestible amino acids rather than total (Khaksar and Golian, 2009). In this regard, there have been a number of papers demonstrating the advantages of using digestible rather than total amino acids to formulate broiler diets (Maiorka et al, 2004(Maiorka et al, , 2005Farrell et al, 1999). However, no reports on the interaction between this method of amino acid formulation and the use of soybean oil with dietary bile salts found in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%